2‐Azidoethane‐1‐sulfonylfluoride (ASF): A Versatile Bis‐clickable Reagent for SuFEx and CuAAC Click Reactions. Issue 8 (14th February 2019) - Zhang, Xu; Moku, Balakrishna; Leng, Jing; Rakesh, K. P.; Qin, Hua‐Li
Abstract : A new reagent, 2‐azidoethane‐1‐sulfonylfluoride (ASF), was synthesized from 2‐chloroethane‐1‐sulfonyl fluoride in 50g‐scale with 87 % yield. This novel reagent possesses two selectively clickable functionalities to be used for both CuAAC and SuFEx click reactions. The application of this reagent ASF to the construction of a class of novel 1, 2, 3‐triazole derived S(VI)‐F analogs was achieved in a quick, efficient and atom‐economical manner. Orthogonally clickable construction of a new class of dendrimers was also accomplished. Abstract : 2‐Azidoethane‐1‐sulfonylfluoride (ASF) was used to prepare a unique 1, 2, 3‐triazole‐derived S(VI)‐F library for medicinal chemistry, chemical biology, and drug discovery in a quick, efficient and atom‐economical manner applying click chemistry. A new class of dendrimers was developed using this reagent through orthogonal CuAAC and SuFEx click reactions.